Performance of Sand-Crushed Oyster Shells Blended Fine Aggregates in Concrete: Waste Management Perspective in Nigeria (Nigerian Journal of Technology, 2021)
Pollution of our environment with wastes and the associated harm to our ecosystem and health is of great concern globally. In addition, the unabated mining of sharp sand for concrete with environmental degradation arising therefrom is worrisome. In the Niger Delta region of Nigeria, enormous quantities of oyster shells are being littered along the streets, riverbanks and landfills, after eating the fleshy part as meat. As a means of managing the waste and conserving sand, this study examines the properties of concrete made, using crushed oyster shells (COS) as partial replacement of sand. Sand was partially replaced in concrete with COS at the rate of 0, 5, 10, 15, 20 and 25%. The concrete matrix was cast in a metal cube mold of 150mm3 and cured for 3, 7, 14 and 28 days. A total of 72 cubes were cast in three replicates for each replacement level and each curing period, using a standard mix of 1:2:4 and water-cement ratio of 0.5. The results reveal that the addition of COS reduces the slump of the fresh concrete from 27 mm at 0% to 20 mm at 25%. The addition of COS up to 25% reduced the density of the concrete by 4.05%. The compressive strength slightly reduced as the percentage replacement increased from 0 to 25%. The findings recommend replacement not exceeding 15% that has true slump of 23.5 mm, lighter density of 25.17 kg/m?3 and compressive strength of 26.2 Nmm?2 which are good for concrete works. When sand is partially replaced with COS in concrete, we can confront the environmental degradation arising from indiscriminate disposal of oyster shells, as well as the depletion of sand as non-renewable component of concrete.http://dx.doi.org/10.4314/njt.v40i1.3